PENGGUNAAN PUPUK HAYATI PADAT ORGANIK TERHADAP PERTUMBUHAN DAN BOBOT HASIL PANEN TANAMAN KEMBANG KOL - Siti Amalia, Istia; Rijal Giffari, Fahri; Irianto Mastur, Adhi; Rohimat, Nanang (Universitas Cokroaminoto Palopo, 2025)
Cauliflower (Brassica oleracea var. botrytis L.) is one of the vegetables widely consumed by Indonesian people. Cauliflower productivity in Indonesia has decreased in recent years. Plant growth and production can be influenced by internal factors of the plant itself and external factors such as climate, soil, sunlight intensity, nutrients, and OPT. Fulfillment of plant nutritional needs is done by providing fertilizers, both organic fertilizers (biological and non-biological) and inorganic fertilizers. This study aims to test the use of organic solid biofertilizers on the growth and weight of cauliflower harvests. The research method used was a randomized block design (RAK) consisting of 6 treatments and 4 replications to obtain 24 experimental units. The treatments used were treatment A (100% solid biofertilizer), treatment B (solid biofertilizer + 75% dose of inorganic fertilizer), treatment C (solid biofertilizer + 50% dose of inorganic fertilizer), treatment D (solid biofertilizer + 25% dose of inorganic fertilizer), treatment E (100% dose of inorganic fertilizer), and treatment F (without fertilization/control). The results showed a significant effect on the provision of solid biofertilizer and inorganic fertilizer on plant height, number of leaves, and wet weight of the harvest, while the stem diameter had no significant effect. Meanwhile, there was no significant difference between the treatments of using solid biofertilizer and inorganic fertilizer.